DIGITAL MARKETING PADA UKM : IDENTIFIKASI RISET GAP MELALUI STUDI LITERATUR REVIEW - Rihan Hafizni; Rahmi Fahmy (Sekolah Tinggi Teknologi Industri Padang, 2021)
The development of digitalization is getting faster, along with the growth in internet usage. Data from Kominfo, internet users in Indonesia, grow 10.2 percent annually or around 27 million users, when compared to internet users in the world, Indonesia is ranked 5th. This condition makes a very drastic change in the marketing world, namely a system change from conventional to digital. The need to conduct research on the use of digital marketing in SMEs is very important. The purpose of this study is to develop an understanding of research related to digital marketing in SMEs, and find research gaps in research published between 2015 and 2020. To analyze and reviewing literature on the theme of digital marketing in SMEs, using systematic analysis and classifying published data from marketing journals, economics, business and management journals as well as IT journals that can be accessed online. The results show. There is a research gap in the field of digital marketing, to fill it, research is needed to investigate the opportunities created by digital marketing for SMEs in Indonesia.